Smart HR For Smart School: Mengintegrasikan Teknologi Digital Dalam Administrasi Pendidikan Efisien dan Efektif - Dayu, Tarisa Nirmala (CV. Dalle’ Deceng Abeeayla, 2025)
This study aims to analyze how the digital transformation of human resources (HR) can improve the efficiency and effectiveness of administration in educational institutions. This research employs a qualitative approach using a case study method. Data were collected through interviews with HR staff at SMK Darussalam Blokagung, as well as through documentation studies and observations. The analysis uses an interactive three-model approach. The results show that digital HR transformation can enhance administrative efficiency, particularly in recruitment processes, employee data management, payroll, and training. The use of Human Resource Information Systems (HRIS) enables the automation of routine tasks, reduces human errors, and accelerates administrative processes. Moreover, digital transformation also improves administrative effectiveness by providing more accurate and relevant data and information for decision-making. This study contributes to identifying and analyzing the impact of digital transformation on the human resource function in schools, particularly in enhancing administrative efficiency and effectiveness.